FACEBOOK SEBAGAI MEDIA BARU TAFSIR AL-QURAN DI INDONESIA: (Studi Atas Penafsiran al-Qur’an Salman Harun) - Muhammad, Wildan Imaduddin (MAGHZA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2017)
This article analyzes the product of Salman Harun's Qur'anic interpretation with Facebook as the medium. As one of the senior professors who pursue the field of interpretation, he has managed to follow the times by utilizing internet technology. There are two focus areas in the study; the first aspect of the sense of Indonesian tafsir attached to the self of Salman Harun, the two aspects of the novelty of discourse that became the basic character of social media. Both aspects are interesting to be studied with a hermeneutic approach. Given that the methodological problem that often arises from the hermeneutic approach is the context of the interpreter that is difficult to trace accurately, then this article finds its relevance to the case of Salman Harun's interpretation which uses the facebook media as the actualization of its interpretation product.